Targeting Repulsive Guidance Molecule A to Promote Regeneration and Neuroprotection in Multiple Sclerosis - Elena Demicheva; Yi-Fang Cui; Philip Bardwell; Stefan Barghorn; Martina Kron; Axel H. Meyer; Martin Schmidt; Björn Gerlach; Mary Leddy; Eve Barlow; Elizabeth O’Connor; Chee-Ho Choi; et al. (Cell Reports, 2015)
Repulsive guidance molecule A (RGMa) is a potent inhibitor of neuronal regeneration and a regulator of cell death, and it plays a role in multiple sclerosis (MS). In autopsy material from progressive MS patients, RGMa was found in active and chronic lesions, as well as in normal-appearing gray and white matter, and was expressed by cellular meningeal infiltrates. Levels of soluble RGMa in the cerebrospinal fluid were decreased in progressive MS patients successfully treated with intrathecal corticosteroid triamcinolone acetonide (TCA), showing functional improvements. In vitro, RGMa monoclonal antibodies (mAbs) reversed RGMa-mediated neurite outgrowth inhibition and chemorepulsion. In animal models of CNS damage and MS, RGMa antibody stimulated regeneration and remyelination of damaged nerve fibers, accelerated functional recovery, and protected the retinal nerve fiber layer as measured by clinically relevant optic coherence tomography. These data suggest that targeting RGMa is a promising strategy to improve functional recovery in MS patients.